Given
• f = -4
,
• g = -g
,
• h = -f
Step-by-step explanation
Let us find the values of g and h.
• Since we know the value of, we can find the value of h.
![\begin{gathered} h=-f \\ h=-(-4) \\ h=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yiranlqyvl1blu56h0odlo8pbz9wk4kxtr.png)
• We solve the given equation for g.
![\begin{gathered} g=-g \\ \text{ Add g from both sides} \\ g+g=-g+g \\ 2g=0 \\ \text{ Divide by 2 from both sides} \\ (2g)/(2)=(0)/(2) \\ g=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/u9ophbmgtrg7vfm2b0bybnw3c5auf4c431.png)
Answer
Therefore, the number line that shows correctly the values of f,g, and h is the one in option c.